MEMAHAMI KEMBALI PELAYANAN PUBLIK UNTUK MEWUJUDKAN TATA PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) - Indriastuti Indriastuti (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2020)
In re-understanding Public Services to realize good governance it will be easy to do if through the public service sector. Fundamentals of Public Services are: 1) Public services are the rights of citizens as a mandate of the constitution, thus it becomes the government's obligation to administer them either by themselves (by the government bureaucracy) or in collaboration with the private sector; 2) Public services are carried out with taxes paid by citizens state. The renewal of the delivery of public services can be used as an entry point and at the same time as a major driver in driving changes in Good Governance practices in Indonesia. Simplification of the bureaucracy can encourage government bureaucracy to return to its main mission of ensuring citizens' access to basic services, the need for collectivity, and other strategic services that are beneficial for a decent and dignified life. (Dwiyanto, 2018) Public Service Reform through System Development and Management of Public Services is very urgent, given the decentralized Unitary Republic of Indonesia (NKRI), so the service system must be able to guarantee equal access of all citizens to public services wherever they live. The system must be able to make the region able to respond to the diversity of the needs of goods and services as a result of regional diversity. As a result of this response allows discretion in the area. Updating public services through Information and Communication Technology is also very important. Public Service Reform can be done as far as there is concern from all stakeholders interests to make it happen.